Novel Coronavirus Infection – Knowns and Unknowns with Particular Reference to Oncology – Combating against COVID-19 with “COVID” - Tsang, Janice; Bajpai, Jyoti (Indian Journal of Medical and Paediatric Oncology, 2020)
We are facing yet another global pandemic with the novel coronavirus (COVID-19) outbreak and anticipate that second and even third wave of the infection may come if we do not practise constant vigilance! An advent of a mysterious outbreak of atypical pneumonia in December 2019, traced from the seafood wholesale market in Wuhan of China, spread the wings over the world in very short span. Like both severe acute respiratory syndrome coronavirus (CoV) and MERS-CoV infections, the risk of severe disease increases substantially with age and with the presence of underlying conditions. While cancer is a prevalent disease and a global health challenge, little information is available with regard to the implications of COVID-19 for cancer patients. So far, the data have been limited and fragmented. COVID-19 with different primary cancer types will have different biological behaviours with highly variable disease courses and diverse treatment strategies. Any generalized conclusions for all cancer patients with respect to COVID-19 should be interpreted with caution until we have sufficient prospective data. Enormous work needs to be done to study the specific unmet needs of cancer patients with the challenge of the COVID-19; the prevention still is the best remedy. Infection control measures should be enforced continuously, and public health education and engagement should be highly recommended. We propose to join hands together to combat against COVID-19 with some simple tips for our cancer patients to raise their awareness of this public health challenge – combating against COVID-19 with “COVID:” Continue “social distancing;” Omit unnecessary face-to-face meting or meal gathering or mass event, make use of cyber meeting, and bring one's own lunch box to work; Visage protection, i.e. universal precaution with surgical masks when going out in a large crowd such as public transport or any close contact in high-risk area; Infection control of the hands with hand hygiene at all times and; Diet, lifestyle, and exercise continue to be balanced and healthy.
Keywords: Cancer; COVID-19; novel coronavirus; oncology